Sickle Cells Abolish Melanoma Tumorigenesis in Hemoglobin SS Knockin Mice and Augment the Tumoricidal Effect of Oncolytic Virus In Vivo - Sun, Chiang Wang; Willmon, Candice; Wu, Li-Chen; Knopick, Peter; Thoerner, Jutta; Vile, Richard; Townes, Tim M.; Terman, David S. (Frontiers in Oncology, 2016)
Insights from the study of cancer resistance in animals have led to the discovery of novel anti-cancer pathways and opened new venues for cancer prevention and treatment. Sickle cells (SSRBCs) from subjects with homozygous sickle cell anemia (SCA) have been shown to target hypoxic tumor niches, induce diffuse vaso-occlusion, and potentiate a tumoricidal response in a heme and oxidant dependent manner. These findings spawned the hypothesis that SSRBCs and the vasculopathic microenvironment of subjects with sickle cell anemia (SCA) might be inimical to tumor outgrowth and thereby constitute a natural anti-tumor defense. We therefore implanted the B16F10 melanoma into humanized hemoglobin SS knockin mice which exhibit the hematologic and vasculopathic sequelae of human sickle cell anemia. Over the 31 day observation period, hemoglobin SS mice showed no significant melanoma outgrowth. By contrast, 68-100% of melanomas implanted in background and hemoglobin AA knockin control mice reached the tumor growth endpoint (p<0.0001). SS knockin mice also exhibited established markers of underlying vasculopathy, e.g., chronic hemolysis (anemia, reticulocytosis) and vascular inflammation (leukocytosis) that differed significantly from all control groups (p<0.0001). Genetic differences or normal AA gene knockin do not explain the impaired tumor outgrowth in SS knockin mice and point instead to the chronic pro-oxidative vasculopathic network in these mice as the predominant cause. In related studies we demonstrate the ability of the sickle cell component of this system to function as a therapeutic vehicle to potentiate the oncolytic/vasculopathic effect of RNA reovirus. Sickle cells were able to efficiently adsorb and transfer the virus to melanoma cells where it induced apoptosis even in the presence of anti-reovirus neutralizing antibodies. In vivo SSRBCs along with their viral cargo rapidly targeted the tumor and initiated a tumoricidal response exceeding that of free virus and similarly loaded normal RBCs without toxicity (p=0.0003). Collectively, these data unveil two hitherto unrecognized findings: Hemoglobin SS knockin mice appears to present a natural barrier to melanoma tumorigenesis while SSRBCs demonstrate therapeutic function as a viable vehicle for enhancing the oncolytic effect of free reovirus against established melanoma.